Konsep Interaksi Sosial Asosiatif dalam Al-Qur’an (Studi Komparatif Tafsīr Al-Munīr Dan Tafsīr Al-Mīṣbaḥ): Studi Komparatif Tafsīr Al-Munīr dan Tafsīr Al-Mīṣbaḥ - Andari, Tiwi; Mushodiq, M. Agus; Nur Amin, Muhammad (Jurnal Penelitian Ilmu Ushuluddin, 2026)
This study examines the concept of associative social interaction in the Qur’an through a comparative analysis of the interpretations by Wahbah az-Zuhaili in Tafsīr Al-Munīr and M. Quraish Shihab in Tafsīr al-Miṣbāḥ, as well as examining its relevance to social interaction theory according to Ahmad Siddiq and Soerjono Soekanto. This study is motivated by the importance of understanding Qur’anic social values in fostering harmonious social relationships within today’s modern society. The method employed is qualitative research using a comparative exegesis approach. The results of the study indicate that the concept of associative social interaction in the Qur’an is reflected in the values of ta‘āwun (cooperation), ta‘āruf (getting to know one another), and social responsibility, as contained in the ijtimā‘iyyah verses. Both exegetes agree that social interaction must be grounded in goodness and piety. The difference lies in the fact that Wahbah Az-Zuhaili places greater emphasis on rules and legal consequences, whereas M. Quraish Shihab emphasizes humanistic values and their application in contemporary life. Furthermore, this concept has strong relevance to the thought of Ahmad Siddiq through his Trilogy of Ukhuwwah as well as Soerjono Soekanto’s theory of associative social interaction. Thus, the social values in the Qur’an can be applied in daily life to build a society that is peaceful, harmonious, and mutually respectful.